Case Report: Hidden Oral Squamous Cell Carcinoma in Oral Somatic Symptom Disorder - Suga, Takayuki; Tu, Trang Thi Huyen; Takenoshita, Miho; Mikuzuki, Lou; Umezaki, Yojiro; Shimamoto, Hiroaki; Michi, Yasuyuki; Hong, Chaoli; Abiko, Yoshihiro; Ikeda, Tohru; Uzawa, Narikazu; Harada, Hiroyuki; et al. (Frontiers in Psychiatry, 2021)
Background: Burning mouth syndrome (BMS) is a common condition of predominant oral pain without evident cause, that maxillofacial surgeons and otolaryngologists often refer to psychiatrists as somatic symptom disorder. In very rare cases, its typical burning symptom mimics those of other diseases in which serious fatal comorbidities may be missed. We encountered three rare cases of oral squamous cell carcinoma (OSCC) with the first symptom of burning tongue. Case presentation: Case 1: A 68-year-old woman had burning pain on the left lingual margin for 8 years. Antidepressant treatment was not efficacious. Cytology and biopsy revealed OSCC. Case 2: A 70-year-old man had burning sensation and paralysis of the tongue for 6 months. Magnetic resonance imaging (MRI) revealed a 37×23-mm mass under the floor of the mouth and enlargement of lymph nodes on both sides. Case 3: A 90-year-old man had burning sensation of the tongue for 1 year. MRI revealed a 12×12-mm mass on the mandible with bone absorption. Conclusion: This case series suggests that psychiatrists must always be careful in regarding BMS as somatic symptom disorder and be cautious of the possibility of OSCC, especially in elderly patients.